OPTIMALISASI SISTEM WAKTU SERVICE ENGINE DAN P2H PADA ALAT BERAT OHT CAT 777 DI PT. SAPTAINDRA SEJATI SITE ADMO KALIMANTAN SELATAN - Darsini, Darsini; Muklis Nurcholic, Agung (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2023)
PT. Saptaindra Sejati is a coal contractor that has a fleet of heavy equipment Dump trucks OHT Cat 777, used to transport coal mining materials from the mining location to the precessing location. In order to support operasional activities, a good fleet of heavy equipmeny id needed equipment id needed so that the coal production target is achieved properly, a maintenance process is needed, because the condition of tne Dump Truck OHT Cat 777 still often experiences damage. With the aim of optimizing the engine service time system and P2H on the OHT Cat 777 heavy equipment. The methods used are PERT and CPM. The results of the analysis with the PERT method are 173,3 minutes, while using the CPM method 170 minutes with the critical path A-B-C-D-E-F-G-H-I-K-L-M-N-O-P-Q-R. In the p2H activity, the engine area uses the PERT method 72,99 minutes while with the CPM method 72 minutes. The critical path generated from both methods has similarities, namely A-H-I-K-G-J-L. The CPM method is faster in terms of work duration and better in its application. The influencing factor is the sequence of work that is adjusted to the network planning so that workers and companies can know which activities need to be prioritized so that there are no delays in completing service engine and P2H activities